Harold Victor Serson (1926-1992) - Jeffries, Martin O. (ARCTIC, 1992)
. Harold first went to the Arctic in 1944 as a Hudson's Bay Company seaman aboard the Nascopie. Thus began a lifelong association with the Arctic. In 1945 he joined the Department of Transport as a radiosonde technician. In 1947 he transferred to the Defence Research Board (DRB) Radio Propagation Laboratory and was one of the first people to winter-over at the newly established joint Canada-U.S.A. weather station at Resolute Bay. Subsequently, he became involved in ionospheric research at the DRB Radio Physics Laboratory, the Prince Alberta Radar Laboratory and the Telecommunications Establishment. As a technician and later technical officer he coauthored a number of papers on radio propagation in the auroral zone. In 1961, Harold was asked to investigate the abandoned Soviet drifting station NP-7, then located in Baffin Bay. That experience led to a meeting with Dr. G. Hattersley-Smith, of the DRB Directorate of Physical Research, and a significant career change. Harold began working in High Arctic oceanography and glaciology and quickly established a reputation in remote arctic science operations and logistics. . In 1981 he retired from government service. However, he was not the type of person who could ever properly retire and turn his back on his beloved Arctic, as I was fortunate enough to soon learn. I was privileged to be able to work with Harold throughout the 1980s, . I shall always remember the experiences we had together and will always be indebted to Harold for his friendship and the knowledge he passed on to me. . He was modest about his achievements, never expected any reward other than thanks, and never sought any honours. In 1988 he was elected a Fellow of AINA in recognition of his significant contributions to High Arctic research. This was the least that could be done for someone who served Canadian arctic science with quiet dedication for almost five decades. Harold will be missed but, I hope, not forgotten.